A corpus-assisted discourse study on the construction of obesity in Indonesian news media - Al Fajri, Muchamad Sholakhuddin; Abdul Rahim, Hajar; Rajandran, Kumaran (Studies in English Language and Education, 2023)
Obesity is one of the health issues that is susceptible to discursive contestation and negotiation. The way it is portrayed in news media can affect public opinions and policymakers. This study aims to investigate the construction of obesity in Indonesian online news media over a five-year period (2017-2021). The analysis was based on a corpus consisting of 1.418 news articles that mentioned the word obesitas (obesity) by drawing upon corpus-assisted discourse study framework and legitimation theory. The findings showed that obesity was predominantly constructed as a problem of personal responsibility, where individuals were viewed as solely responsible for minimising the risk of obesity and its associated health issues by losing or regulating their weight. This was frequently legitimised through expert authority by referring to medical experts interviews, or through impersonal authority by referring to scientific research. Meanwhile, the societal responsibility discourse which focused on the role of government and the food industry in creating conditions that led to obesity was very scarce. It is argued that this may reflect the presence of prevailing neoliberal ideology in Indonesian society. More balanced reporting, therefore, is recommended to lessen the stigmatisation of people with obesity and to recognise the variety of determinants of and solutions to obesity, reflecting its complexity more accurately.